Selectivity and control of Euphorbia heterophylla in sugarcane by herbicide in post-emergence - Araldi de Castro, Rosilaine; de Castro, Sérgio Gustavo Quassi; Quassi de Castro, Saulo Augusto; Piassa, Alexandre; Pedrosa, Sandro Gonçalves; Tropaldi, Leandro [UNESP] (Taylor & Francis, 2023)
To obtain good control of wild poinsettia (Euphorbia heterophylla) in post-emergence in sugarcane crop, we evaluate the herbicides association on post-emergence of E. heterophylla and the ratoon cane selectivity. The experimental scheme was in randomized blocks with 6 treatments and 4 replications. The treatments were: control; ametryn + mesotrione + sulfentrazone (1,500 + 144 + 800 g i.a ha−1); ametryn + mesotrione + diclosulan (1,500 + 144 + 200 g i.a ha−1); ametryn + mesotrione (2,500 + 144 g i.a ha−1: Highest dose); ametryn + mesotrione (2,000 + 144 g i.a ha−1: Lowest dose) and ametryn + mesotrione + diuron (1,000 + 144 + 1,250 g i.a ha−1). The percentage of control, dry mass, height and percentage of germination of E. heterophylla and injury level, yield and technological quality of sugarcane were evaluated. The best control of E. heterophylla was: ametryn + mesotrione +sulfentrazone; ametryn + mesotrione + diclosulan and ametryn + mesotrione (Lowest dose). As for the ratoon cane selectivity the best yield was achieved with the association ametryn + mesotrione +diclosulan. An appropriate association of herbicide molecules provides successful control of E. heterophylla, especially the association of sulfentrazone or diclosulan together with ametryn and mesotrione.
Keywords: Ametryn; diclosulan; diuron; mesotrione; sulfentrazone